Measurement of the t(t)over-bar production cross section in the all-jets final state in pp collisions at root s=8TeV - (:unkn) unknown (SPRINGER, 2016)
The cross section for tt production in the all-jets final state is measured in pp collisions at a centre-of-mass energy of 8 TeV at the LHC with the CMS detector, in data corresponding to an integrated luminosity of 18.4 fb(-1). The inclusive cross section is found to be 275.6 +/- 6.1 (stat) +/- 37.8 (syst) +/- 7.2 (lumi) pb. The normalized differential cross sections are measured as a function of the top quark transverse momenta, pT, and compared to predictions from quantum chromodynamics. The results are reported at detector, parton, and particle levels. In all cases, the measured top quark pT spectra are significantly softer than theoretical predictions.